2020
DOI: 10.1055/s-0039-3399570
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myxoma with Cerebral Metastases and Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma: A Case Report and Review

Abstract: Background Cardiac myxomas, the most common primary cardiac tumors, are generally benign neoplasms. Primary cardiac lymphoma is a rare cardiac malignancy with a very poor prognosis. Here we present a case of a cardiac myxoma with cerebral metastases and chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) arising within the cerebral metastases. Case description A 62-year-old man, who presented with symptoms of multiple transient ischemic attacks, was found to have a left atrial myxoma. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Although the mechanisms of embolization of a benign tumor and metastasis of an invasive malignancy are fundamentally different, the appearance of multiple lesions at a distant site in the setting of a cardiac myxoma has occasionally been referred to (erroneously) in the literature as “metastasis.” 17,18 Since the first description made by Rankin et al ., in 1978, 19 our comprehensive review revealed 36 histologically established cases of intracerebral embolization associated with parenchymal brain invasion from a benign left atrial myxoma (Table 1). 10,14,18–51 A careful review of the cases confirmed that three patients have been reported twice, 14,19,20,23,24,28 six patients had unavailable histological proof, 37,52–56 and four apparent primary cardiac sarcomas were erroneously reported as a cardiac myxoma 57–60 . In one case, the original report could not be located, 61 and another report described embolic myxoma cells in the leptomeninges without evidence of parenchymal seeding 62 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the mechanisms of embolization of a benign tumor and metastasis of an invasive malignancy are fundamentally different, the appearance of multiple lesions at a distant site in the setting of a cardiac myxoma has occasionally been referred to (erroneously) in the literature as “metastasis.” 17,18 Since the first description made by Rankin et al ., in 1978, 19 our comprehensive review revealed 36 histologically established cases of intracerebral embolization associated with parenchymal brain invasion from a benign left atrial myxoma (Table 1). 10,14,18–51 A careful review of the cases confirmed that three patients have been reported twice, 14,19,20,23,24,28 six patients had unavailable histological proof, 37,52–56 and four apparent primary cardiac sarcomas were erroneously reported as a cardiac myxoma 57–60 . In one case, the original report could not be located, 61 and another report described embolic myxoma cells in the leptomeninges without evidence of parenchymal seeding 62 …”
Section: Discussionmentioning
confidence: 96%
“…63 Thus, parietal and occipital lobes are the most affected regions (91.6%). Moreover, the bone 19,35,46 and the skin 23,50 can be simultaneously involved. The most common clinical presentation of these patients was seizures (37.1%), followed by headache (31.4%), and hemiparesis (20%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of case reports from the last 20 years conducted by Maas et al. [9] revealed that there have been 22 cases of cardiac lymphomas arising within cardiac myxomas. Another case reported by Park et al.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Radiation therapy has also been used in patients with multiple metastases, usually whole-brain radiation at 25–30 Gy. [ 5 ] Postoperative chemotherapy with either ifosfamide and doxorubicin or doxorubicin alone has also been attempted in patients with multifocal disease, though with mixed results. [ 7 ] One case report even documents the use of Gamma Knife radiosurgery to treat cerebral metastases, without recurrence of disease 2 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%